Variabilidade genotípica dos isolados de Giardia duodenalis em diferentes espécies de animais - Fava, Natália de Melo Nasser (2013)
Giardia duodenalis is parasite of small intestine of several mammalian species, including humans, and it is found worldwide. Among domestics and wild animals this specie is prevalent regardless of race, sex, age and fitness, with significant clinical and economic importance. For a long time the parasite was considered specific for the host where it was found, but recently it was observed the existence of a relationship between assemblage of isolate and its host. Currently, G. duodenalis have been considered a complex, and molecular characterization of parasite isolates is critical for the knowledge about the transmission of giardiasis. Different results have been identified when various loci are sequenced, therefore, multilocus genotyping becomes the main ally in the trusted attribution of assemblages/subassemblages to the isolates. The aim of this study was to genetically characterize G.duodenalis cysts from dogs, cattle, pigs and lambs from kennels, pet shops, and farms from microregion of Uberlândia, using four markers. To determine the positivity of G. duodenalis cysts a flotation technique was employed. For genotyping, the genes glutamate dehydrogenase (gdh), triose phosphate isomerase (tpi), β-giardin (bg) and SSU-rRNA was used. Cysts of G.duodenalis were found in dogs, cattle, pigs and lambs and the infection rates were 21,66%, 18,75%, 5.5% e 24,8%, respectively. In association between positivity and sex, age, race and fitness, only age was significant regarding the infection. Fragments of gdh, tpi and bg was amplified in 33,3%, 36,8 and 7,2% of samples, respectively. PCR detection of SSU- rRNA failed to amplify and to sequence DNA samples. A total of 70 sequences were obtained, 34 (48,6%) from gdh, 25 (35,7%) from tpi and 11 (15,7%) from bg. The predominace of host-adapted assemblages was observed in all genes, and tpi was the only gene that classified isolates as zoonotic assemblage. Heterogeneous samples were found in gdh (pigs) and tpi (cattle and lambs). On multilocus genotyping (MLG) only three samples demonstrated concordance using the three genes, thus it was not possible to establish any relationship between assemblage and the variables sex, age, race fitness and fecal score.